Formulation, physicochemical, and sensory evaluation of cookies prepared from Sacha Inchi Oil Meal (SIOM) - Christopher, Jeffi; Tan, Chin Ping; Wasoh, Helmi; Tang, Teck-Kim; Lee, Yee-Ying; Lai, Oi Ming (Universiti Putra Malaysia, 2024)
Due to its substantial amounts of essential amino acids and protein, sacha inchi oil meal (SIOM) is ideal for producing protein-rich food. This study developed the cookies by blending SIOM with wheat flour at 5, 10, 20, and 30% (w/w), respectively. Physical properties, proximate composition, and sensory study were evaluated on the cookies. Data showed that 10% of wheat flour-SIOM cookies had the highest protein content (13.03%) compared to wheat flour cookies (4.89%). Cookies made with 20 and 30% SIOM were also feasible as the crude fiber content was high (48%). The hardness of wheat flour-SIOM incorporated cookies was lower (2.52–3.22 N) than wheat flour cookies (3.30 N). The water activity value of all the cookie samples during the 30-day storage was less than 0.6, indicating that the product was stable. Sensory analysis showed that the panelists preferred 10% SIOM-blend cookies over commercial cookies because of their better color, sweetness, texture, and appearance. Moreover, the overall acceptability of SIOM cookies was greater than 6 on a 9-point hedonic scale. This study concludes that SIOM can be a functional food ingredient that can help develop healthier bakery products.